Analysis of Student Difficulties in Early Writing Learning at the Elementary School Level - Fahira, Winda; Iswara, Prana Dwija (Universitas Negeri Semarang, 2023)
Beginning writing skills are a crucial aspect of language learning at the primary school level. However, many students encounter difficulties in developing these skills during this early stage. This study aims to analyze students' struggles in learning to write at the elementary school level, with the purpose of understanding and addressing these challenges. The research conducted reveals that students' initial writing skills are still at a low level. Based on the analysis of 16 indicators of writing difficulty, it was found that 22% of students had no difficulty, 19% faced minor difficulties, 31% encountered considerable difficulties, and 28% experienced significant difficulties. Among these indicators, three were rated as relatively good: holding a pencil, writing in a straight line, and the overall legibility of writing, with percentages of 33.3%, 33.3%, and 30%, respectively. The remaining 13 indicators fell into the category of minor, moderate, or severe difficulty. This clearly indicates that many students still struggle with writing skills. The study underscores the importance of addressing these early writing difficulties to ensure students' progress in this essential aspect of language learning.